قربانی: ایک شرعی عبادت، عصر حاضر میں اہمیت اور چیلنجز: Qurbānī: A Sharīʿah-ordained Act of Worship, Its Contemporary Significance, and Challenges - Gul Rukh Irfan; Saba; Zainab Bibi (Corresponding Author) (International Research Journal of Arabic and Islamic Studies, 2024)
Qurbani, or sacrifice, holds significant importance in Islamic tradition, particularly during the occasion of Eid al Adha. The obligation of Qurbani is contingent upon certain conditions that must be met by an individual. Firstly, the person intending to offer Qurbani must be a sane adult Muslim who is financially capable of performing the act. Financial capability refers to owning wealth above the threshold of Nisab, the minimum amount of wealth one must possess for Zakat, another pillar of Islam, to be obligatory. Additionally, the individual should possess ownership of the animal intended for sacrifice, or have the right to sacrifice on behalf of another person, such as a family member. Furthermore, the animal itself must meet specific criteria. It should be of an eligible species, such as sheep, goat, cow, or camel, and must be free from any physical defects that render it unsuitable for sacrifice. Animals should also be of a certain age, generally past the age of maturity, to ensure their suitability for sacrifice. From a jurisprudential perspective, the obligation of Qurbani serves multiple purposes. It symbolizes obedience to Allah's commands and demonstrates gratitude for His blessings. Additionally, it promotes empathy towards the less fortunate by distributing meat among the needy, thus fostering social cohesion and compassion within the community. This paper explores the conditions under which Qurbani becomes obligatory in Islam and provides a jurisprudential assessment of its implications. And examined the challenges faced in the modern era.